2015
DOI: 10.1371/journal.pone.0142374
|View full text |Cite
|
Sign up to set email alerts
|

Spaceflight Effects on Cytochrome P450 Content in Mouse Liver

Abstract: Hard conditions of long-term manned spaceflight can affect functions of many biological systems including a system of drug metabolism. The cytochrome P450 (CYP) superfamily plays a key role in the drug metabolism. In this study we examined the hepatic content of some P450 isoforms in mice exposed to 30 days of space flight and microgravity. The CYP content was established by the mass-spectrometric method of selected reaction monitoring (SRM). Significant changes in the CYP2C29, CYP2E1 and CYP1A2 contents were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In this study, we did not perform quantitative validation using a targeted mass-spectrometry technique. However, Cyp1a1 and Cyp2d9 up-regulation, as well as Cyp3a11 down-regulation is consistent with our previous data on CYP450 absolute abundance obtained by selected reaction monitoring (SRM) with isotopically labeled peptide standards on the same animals (mice from flight, post-flight, and ground control group) [ 22 ]. Label-free quantification is a promising approach due to low-cost and using of high-resolution mass-spectrometers, which yields high precise measurements of several peptides per protein (at least three unique peptides in our study).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we did not perform quantitative validation using a targeted mass-spectrometry technique. However, Cyp1a1 and Cyp2d9 up-regulation, as well as Cyp3a11 down-regulation is consistent with our previous data on CYP450 absolute abundance obtained by selected reaction monitoring (SRM) with isotopically labeled peptide standards on the same animals (mice from flight, post-flight, and ground control group) [ 22 ]. Label-free quantification is a promising approach due to low-cost and using of high-resolution mass-spectrometers, which yields high precise measurements of several peptides per protein (at least three unique peptides in our study).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, recovery of other elevated CYP levels was shown, which indicates reconstitution of the hepatic pharmacological response. Our results of reconstituted levels of Cyp1a2 underline previously detected elevated levels of cytochrome P450 1A2 during flight compared to post-flight [ 22 ], showing the importance to monitor liver performance during flights. Numerous drugs are turned over in the liver by CYP1A2 [ 23 ] illustrating its immense clinical importance.…”
Section: Discussionsupporting
confidence: 82%
“…25 More recently, Moskaleva et al demonstrated a significant increase in P450 enzyme concentration after 30 days of spaceflight in four flown mice. 44 Other recent studies have identified altered enzyme activity, such as increased lipotoxic activation 45 and increased autophagy and proteasome activity, 46 in flown mice.…”
Section: Spaceflight Pharmacokinetics and Pharmacodynamicsmentioning
confidence: 96%
“…There have been a number of excellent publications either as reviews [1,[82][83][84][85][86][87][88][89] or as original research, including publications which illustrate the effect of gravity on drug targets, processes which affect drug behavior in physiological systems [72,73,86,[89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104] and this section will summarise the major findings. When planning astronaut healthcare for a space mission, there are a number of basic considerations which are, in part dependent upon the duration of the mission;…”
Section: Use Of Medication In Space Travelmentioning
confidence: 99%